1995
DOI: 10.1111/j.1365-2273.1995.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the mechanism of snoring using sleep nasendoscopy

Abstract: We have performed sleep nasendoscopy on 54 adult snorers in whom obstructive sleep apnoea had been excluded by an overnight sleep study. The purpose of the study was to identify the site or sites of noise production in each case. This was successfully achieved in 50 of the 54 and 70% showed palatal flutter snoring only. In a further 20%, palatal flutter snoring was combined with evidence of noise generation at another site. The second site was supraglottic in 10%, tonsillar in 8% and tongue base in 2%. The ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1
10

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 7 publications
4
85
1
10
Order By: Relevance
“…This result does not correspond with that of Quinn et al [6], who observed the sources of snoring using DISN in 50 patients with SS and found that 70% of the patients snore due to palatal fluttering only (type I), and 20% due to palate fluttering combined with evident vibration of the epiglottis (10%), tonsils (8%), and tongue (2%). Sole tongue base vibration and sole epiglottis vibration, which were not observed in our study, was seen in 8 and 2% of the patients, respectively.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This result does not correspond with that of Quinn et al [6], who observed the sources of snoring using DISN in 50 patients with SS and found that 70% of the patients snore due to palatal fluttering only (type I), and 20% due to palate fluttering combined with evident vibration of the epiglottis (10%), tonsils (8%), and tongue (2%). Sole tongue base vibration and sole epiglottis vibration, which were not observed in our study, was seen in 8 and 2% of the patients, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…1c). Rapid occlusion and reopening of the aperture or the slit could be observed during inspiration [6]. On the other hand, the epiglottis and the tongue base vibrated with slight amplitude in most patients; concurrent collapse during vibration was also slight or negative.…”
Section: Resultsmentioning
confidence: 99%
“…epiglottis, may also vibrate to a greater or lesser extent in any one individual [8]. In these circumstances, it is no surprise that the present authors found that treatment directed at the soft palate did not abolish snoring in any of the patients, even temporarily.…”
Section: Discussionmentioning
confidence: 54%
“…Although snoring can arise from the vibration of many structures in the upper airway, the soft palate is considered to be the major sound generator [6][7][8]. Based on this assumption, various types of palatal surgical techniques have been developed.…”
mentioning
confidence: 99%
“…Even though it tries to simulate what happens during sleep, it may result in mistaken interpretations, given that the patient that is awaken does not relax the central command he/she has 16 .…”
Section: Discussionmentioning
confidence: 99%